How is the Application of Green Accounting in Public Hospitals Based on the Public Hospital Classification? - Muhammad Hasyim Ashari (International Journal of Integrative Sciences, 2023)
Public hospitals have four classification (types/class): A, B, C, and D. Of course, the application of green accounting in public hospitals has differences in its application depending on the type of public hospital. The purpose of this study is to determine whether there are differences in the application of green accounting in public hospitals in Malang Raya between public hospitals with type A, type B, type C or type D. This research is a survey research with a descriptive quantitative approach. The questionnaires collected were 39 research samples from 40 public hospitals spread across Malang District, Malang City and Batu City. The sample selection used a probability sample with a cluster random sampling technique. The collected data was then analyzed using the Kruskal-Wallis Test and the Turkey HSD Test. The results showed that the average value of the application of green accounting was significantly different for each type of public hospital, whether for type A, type B, type C or type D on public hospitals. The most visible difference was in the application of green accounting to public hospitals type A and public hospitals type C are completely different, while everything else is the same